Entrepreneurial attitude and economic growth; a cross-section of 54 regions - Sjoerd Beugelsdijk; Niels Noorderhaven (European Regional Science Association (ERSA), 2002)
Over the past ten years the concept of regional clustering has gained much popularity in business, government, and the academic world. In regional economics, much attention has been devoted to explain the economic success of certain regions all around the world. Theoretical concepts like industrial districts, regional innovation systems and the learning region link the geographical concentration of firms and regional institutions to the innovativeness of these firms. Terms like 'regional innovative capacity' (Lawson and Lorenz, 1999), 'enterprise culture' (Amin and Tomaney, 1991), 'entrepreneurial ability' (Kangaharju, 2000), 'entrepreneurial human capital' (Georgellis and Wall, 2000) and 'regional cultures of innovation' (Thomas, 2000) are frequently used in the literature on regional clusters. In general, it is argued that local social conditions play an important role in the genesis and assimilation of innovation and its transformation into economic growth. More specific, entrepreneurial skills are seen as the soft factors that contribute to a regional culture that facilitates the success of regional clusters and regional economies in general.In this paper we test if certain societal characteristics are related to regional economic growth. In specific, we test if regions that can be characterised as 'entrepreneurial', experience faster economic growth than regions that score lower on entrepreneurial characteristics. Despite the growing literature in the field of economic geography and regional economics in which the role of entrepreneurial skills is stressed, to our knowledge nobody has explicated the values that make up this entrepreneurial capital. It is in most cases a black box, which is commonly referred to, but never explicated. Using a unique data-set on norms and values in 54 European regions, we distinguish values that characterise entrepreneurs, which enables us to construct a regional aggregate that reflects the average score on entrepreneurial attitude of the populations in these 54 European regions. The paper is divided in two parts. First, we study entrepreneurs and compare their personality characteristics with those of wage and salary-earners. Based on a sample of 18,418 individuals we find that entrepreneurs differ in several ways. The next step consists of aggregating these characteristics for 54 regions in Europe. By using principal components analysis, we construct a measure of entrepreneurial capital for each region. Based on standard growth theory we test if regions that have more entrepreneurial capital experience faster economic growth in the period 1950-1998. The added value of the paper is twofold. First, we show that entrepreneurs differ from the wage and salary-earners in several ways. Entrepreneurship requires aptitudes that are only present in a small portion of a population. Second, we study 54 regions in Europe and show that regions scoring higher on these entrepreneurial characteristics experience faster economic growth, conditional on factors like human capital, investment ratio and spatial auto-correlation. By unravelling the soft factors influencing economic growth we open the black box of regional culture. There are regional differences in entrepreneurial attitude, and a relatively high score on entrepreneurial characteristics is correlated with a relatively high rate of regional economic growth.
Keywords: 330